Faktor Risiko yang Dapat Diubah pada Demensia Lansia: Ulasan Literatur Naratif Singkat - Hatimi, Fahmi Ilham; Hardiansyah, Ridwan; Islami, Suryadi (CV. Jasa Sukses Abadi, 2025)
The gradual neurological disease known as dementia causes a substantial reduction in cognitive function, which impairs an older person's capacity to carry out everyday tasks on their own. Dementia is a serious worldwide health concern since its prevalence rises with age. Through a narrative literature review, this study seeks to uncover modifiable risk factors for dementia in the elderly. Utilizing the terms